Neuro-ophthalmology Training in Ophthalmology Residency Programs in the United States - Wayman, Laura L.; Chen, John J.; Leavitt, Jacqueline A. (Journal of Academic Ophthalmology, 2018)
Background The status of neuro-ophthalmology education in ophthalmology residency training in the United States is unknown. There are numerous articles in the literature detailing resident outcomes for surgical procedures; however, there are no articles detailing teaching of a nonprocedural specialty. There are no specific Accreditation Council for Graduate Medical Education (ACGME) requirements for neuro-ophthalmology training within ophthalmology residency. Each program determines the amount of neuro-ophthalmology training and level of training within ophthalmology residency. There are no publications that detail the extent of neuro-ophthalmology training during ophthalmology residency.Objective To determine the status of neuro-ophthalmology education in ophthalmology residency training programs in the United States.Methods A survey was sent in 2014 to residency directors and neuro-ophthalmologists of all ophthalmology residency programs who participated in the Ophthalmology Residency Matching Program in the United States to determine the amount of neuro-ophthalmology training that residents receive.Results From a total of 113 ophthalmology residency programs in the United States utilizing the Ophthalmology Residency Matching Program, 104 surveys were returned (92% response rate). Duration of neuro-ophthalmology training ranged from 1 to 112 days, with an average of 34.5 days. Most rotations occurred within postgraduate year 2 or 3.Conclusion This is the first evaluation of the amount of neuro-ophthalmology training within ophthalmology residencies participating in the matching program in the United States, which demonstrates large variability among the different programs. Future studies could ascertain if there is a correlation between resident satisfaction in neuro-ophthalmology training and the amount of training.
Keywords: neuro-ophthalmology; residency; education